Is Failure the Best Option? An Untimely Reflection on Teaching - Stefano Oliverio (University of Bologna, 2023)
After outlining the renascent interest in teaching within contemporary educational theory, the present paper engages with a reflection on teaching beyond the predominant learnification and the related emphasis on efficacy as a primary value. In this endeavour, the theme of teachers' demoralization is introduced in a philosophical-educational key, by deploying an existential perspective. Within this horizon, a special focus is on failure construed as intimately linked with the 'essence' of education qua an encounter of free beings and as a possibility inherent to the dignity of teaching. In conclusion, some implications of this recognition of the 'significance' of failure are indicated in regard to teacher education.